Depression status and functional outcome of patients with ischemic stroke and the impact on caregivers living in Chengdu: a cross-sectional study - He, Lanying; Wang, Jian; Wang, Feng; Wang, Lu; Liu, Yinglin; Zhou, Fanfan; Xu, Fan (Frontiers in Psychiatry, 2023)
Objectives: To investigate the associations between risk factors and depression symptoms in ischemic stroke (IS) survivors, and investigate IS survivors’ depression status and function outcome effect on caregiver burden among the Chengdu. Methods: This was a cross-sectional study; we recruited a convenience sample of ischemic stroke and paired caregiver living in Chengdu from February 2022 to May 2022. Depression symptom was assessed using17-item Chinese Hamilton Depression Rating Scale (HDRS), the Perceived Social Support Scale (PSSS) was used to assess the social support of patients, Zarit burden interview (ZBI) was used to assess caregiver burden. Multivariable logistic regression was used to analyze data between risk factors and depression symptoms, and multiple linear regression models were constructed to examine the stroke survivors’ depression symptoms, and function outcome and caregiver burden. Results: 966 IS survivors and paired caregivers were included in this study, among IS survivors, 35.51% (343/966) experienced depression status. Age (aOR, 1.02; 95% CI, 1.00-1.04; P=0.036), NIHSS (aOR, 1.57; 95% CI, 1.47-1.68; P<0.001), and PSSS (aOR, 0.86; 95% CI, 0.84-0.89; P<0.001) were associated with increased risk of depression status, and NIHSS of patients (b=2.57, P<0.001), depression status of patients (b=2.54, P<0.001), duration of care time (b=0.359, P=0.006), social supports of caregivers (b=-0.894, P=0.038) were significantly associated with ZBI. Conclusions: PSSS were major risk factors for development of depression status in IS survivors, and the depression status and severer functional deficits of patients had negative impact on ZBI of main caregivers, and social support can reduce ZBI